Peran guru kelas II dalam menanamkan sikap toleransi melalui pembelajaran pendidikan pancasila dan kewarganegaraan (ppkn) di sdn glonggong 2 - Achmad Nur Faizin; Ilma Nalurita Rochmani; Saraswati Wulan P.S.M; Zahra Lailatul Nur Alfiani (Prosiding Konferensi Ilmiah Dasar, 2026)
The formation of students' character demands the instillation of tolerance from the elementary school level. Based on this, the study aims to examine the role of teachers in developing tolerance through PPKn (Citizenship Education). The research locus is the second-grade students of SDN Glonggong 2. A descriptive qualitative approach is used. Semi-structured interviews with second-grade teachers become the primary data source. The analysis includes three stages: reduction, presentation, and conclusion drawing. Field findings identify various efforts by teachers. Exemplary behavior, positive habituation, dialogical conflict guidance, and the integration of Pancasila values in learning activities are the strategies implemented to instill tolerance. This process is supported by the application of various strategies, including lectures, providing examples, role-playing, group work, and outdoor learning. The implementation of these strategies has a positive impact on developing mutual respect, cooperation skills, and respect for differences among students. Nevertheless, the process of instilling tolerance still faces challenges such as the limited understanding of students regarding the concept of tolerance and the influence of the family environment on character formation. Therefore, synergy between school and family becomes an important factor in supporting the successful instillation of tolerance attitudes in students.